Core-Periphery Patterns across the European Union. - Duarte, Adelaide (Emerald Publishing Limited, 2017)
In this new work, Pascariu and Duarte, along with an international group of acclaimed scholars, delve into key challenges currently facing the European Union. They Analyze the effect of peripherality across the EU regions which will be of great interest to those countries and regions facing a process of integration.